2023
DOI: 10.3329/bjms.v22i1.61867
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Vaccine Preference and Fear of COVID-19 among Malaysians during the Heightened Phase of COVID-19 Pandemic

Abstract: Objective: The objective of this study was to investigate the knowledge, vaccine preference and fear of COVID-19 among Malaysians. Materials and Methods: This online questionnaire survey was carried out from 6th September 2021 to 12th November 2021 through Google form on adult Malaysians. To collect the data, a pilot-tested validated questionnaire was administered to 387 samples. The questionnaire comprised of participants’ socio-demographic characteristics, knowledge on COVID-19 vaccine with source of informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…18 In a study conducted in Malaysia, the most common source of information about COVID-19 vaccination was reported as social media, with a rate of 85.3%. 19 Only 10.8% in our study answered as health professionals, and TV/radio was reported as the second most common source of information. According to these results, in the pandemic period when infodemic is a serious growing problem 20 , it should be prioritized that the internet and media resources are constantly updated in accordance with scientific facts, and measures should be taken to prevent misinformation so that the public can access accurate and reliable information.…”
Section: Discussionmentioning
confidence: 60%
“…18 In a study conducted in Malaysia, the most common source of information about COVID-19 vaccination was reported as social media, with a rate of 85.3%. 19 Only 10.8% in our study answered as health professionals, and TV/radio was reported as the second most common source of information. According to these results, in the pandemic period when infodemic is a serious growing problem 20 , it should be prioritized that the internet and media resources are constantly updated in accordance with scientific facts, and measures should be taken to prevent misinformation so that the public can access accurate and reliable information.…”
Section: Discussionmentioning
confidence: 60%
“…In Pakistan, a heterogeneity regarding vaccine acceptance rate exists that might be influenced by factors such as effectiveness and possible side effects of the vaccines, which may hinder the success of the immunization campaign [10][11][12] . With 61% of the population fully vaccinated, the country is still behind other countries of the region such as Bangladesh, India, China and Iran where 75 to 90% of the population is fully vaccinated 1 .…”
Section: Discussionmentioning
confidence: 99%
“…A good communication through a trusted media coverage needs to be ensured to get the best results in this regard. 22 Good communications is an art that determines adherence to therapy. 23 Although this study displayed a higher rate of overweight and obesity prevalence in males, other studies showed that females are more prone to obesity than males.…”
Section: Table-1: Sociodemographic Characteristics Of the Participant...mentioning
confidence: 99%